ENHANCING SUSTAINABILITY AND REDUCING CO2 EMISSIONS IN PLASTIC MANUFACTURING THROUGH THE TRANSITION FROM HYDRAULIC TO ELECTRIC INJECTION MOLDING TECHNOLOGY - Soesilo, Rahman; Valentin, Adelia Dwi (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2025)
This study addresses the critical issue of sustainability and CO2 emissions in the plastic manufacturing sector, focusing on the transition from hydraulic to electric injection molding systems. The research is based on a case study of PT. RPI Indonesia, which replaced 21 hydraulic injection molding machines with more efficient alternatives. A quantitative methodology was employed, collecting energy consumption and CO2 emissions data before and after the transition. The findings reveal a significant reduction in energy consumption, approximately 25%, leading to a decrease in CO2 emissions from 5,191.5 tons to 1,934.8 tons annually. This transition not only mitigates environmental impacts but also aligns with global sustainability initiatives. The study concludes that adopting advanced injection molding technologies enhances operational efficiency and contributes significantly to sustainability goals in the plastic manufacturing industry. Future research should explore long-term outcomes of such transitions and further strategies to improve sustainability.